Type 2 diabetes mellitus as an independent risk factor of pulmonary tuberculosis: A hospital based cross-sectional study - Yanti, Budi; Firdausa, Sarah; Irsyah, Abid Dhiyauddin Alfani; Andayani, Novita; Salwani, Desi (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Background: The growing frequency of infectious and non-communicable illnesses on a global scale is primarily associated with the changing patterns observed in epidemiology. Diabetes mellitus (DM) significantly leads to the development of tuberculosis (TB) and less effective treatment outcomes if not identified early. Objective: This study aims to investigate type 2 DM as a risk factor for TB infection.Methods: Participants in this cross-sectional research study comprised DM patients who reported cough complaints at the TB treatment center and the internal medicine department of Zainoel Abidin Hospital. Random blood glucose and glycated hemoglobin (HbA1c) levels were measured in all respondents. The Chi-Square test assesses the association between DM and Pulmonary TB.Results: There are 48 DM patients with new pulmonary TB, an averageage of 53 years (SD 9.1). Most of them have symptoms of cough for more than 2 weeks (85.4%), loss of body weight (77.1%), chest pain (58.3%), and loss of appetite (72.9%). The high HbA1c levels were associated with TB, as detected by Xpert MTB/RIF assay and typical radiographic signs (p<0.05). DM patients with increased HbA1c were found to have a two times chance of showing results from a chest x-ray typical of TB and probability of TB infection (PR: 2.850, 95% CI (1.152-7.053); 2.745, 95% CI (0.969-7.780)) respectively.Conclusion: DM patients had two times the risk of lung damage based on chest X-rays and having TB. DM may seriously compromise the efficacy of TB control programs and impede a nation's progress toward TB elimination.